WOLTERSTORFF’S REFORMED EPISTEMOLOGY - Baker, Deane-Peter (Scriptura, 2009)
This paper offers an analysis of Nicholas Wolterstorff’s contribution to the Reformed epistemology movement, which holds as its central claim the idea that belief in God can, under the appropriate circumstances, be properly basic. In particular this paper addresses Wolterstoff’s arguments for his claim that Christian believers are epistemically entitled to their beliefs. The paper begins by setting out Wolterstoff’s theory, before articulating the main lines of objection that have been raised against Wolterstorff’s arguments. The paper concludes with an analysis of whether or not Wolterstorff’s arguments offer genuine support to the Reformed epistemology project.